Identification of Explosion from Hydrogen Gas - Fithriyyah Karimah; Tico G Samosir; Fuaddinda P Salsabila (Universitas Negeri Medan, 2021)
Hydrogen or sometimes called water, is a chemical element on the periodic table that has the symbol H and atomic number 1. At standard temperatures and pressures, hydrogen is colorless, odorless, non-metallic, singlevalent, and a highly flammable diatomic gas. With an atomic mass of 1.00794 amu, hydrogen is the lightest element in the world. It is also the most abundant element, accounting for roughly 75% of the total elemental mass of the universe. Most stars are formed by hydrogen in the plasma state. Hydrogen compounds are relatively rare and rarely found naturally on Earth, and are usually produced industrially from various hydrocarbons such as methane. Hydrogen can also be produced from water through electrolysis, but this process is more expensive commercially than producing hydrogen from natural gas. With the aim to prove the explosion that occurred and the reaction that occurred during the experimental process of an exothermic or endoderm reaction explosion